The Disulfide Bond between Cys22 and Cys27 in the Protease Domain Modulate Clotting Activity of Coagulation Factor X - Li, Fang; Chen, Changming; Qu, Si-Ying; Zhao, Ming-Zhu; Xie, Xiaoling; Wu, Xi; Li, Lei; Wang, Xuefeng; Ding, Qiulan; Xu, Qin; Wei, Dong-Qing; Wu, Wenman (Thrombosis and Haemostasis, 2019)
The Cys22-Cys27 disulfide bond of factor X (FX) protease domain is not conserved among coagulation factors and its contribution to the physiological haemostasis and implication in the pathogenesis of haemostatic and thrombotic disorders remain to be elucidated. Mutation p.Cys27Ser was identified in a pedigree of congenital FX deficiency and fluorescence labelling study of transiently transfected HEK293 cells showed accumulation of FX p.Cys27Ser within cell, indicating incompetent secretion partially responsible for the FX deficiency. The clotting activity of FX p.Cys27Ser was decreased to about 90% of wild-type, while amidolytic and pro-thrombinase activities (kcat/Km) determined with recombinant FXa mutant were 1.33- and 4.77-fold lower. Molecular dynamic simulations revealed no major change in global structure between FXa p.Cys27Ser and wild-type FXa; however, without the Cys22-Cys27 disulfide bond, the insertion of newly formed N terminal of catalytic domain after the activation cleavage is hindered, perturbing the conformation transition from zymogen to enzyme. The crystal structure of FXa shows that this disulfide bond is solvent accessible, indicating that its stability might be subject to the oxidation/reduction balance. As demonstrated with FX p.Cys27Ser here, Cys22-Cys27 disulfide bond may modulate FX clotting activity, with reduced FX pertaining less pro-coagulant activity.
Keywords: coagulation factor X; Cys27; disulfide bond; oxidation/reduction balance; molecular dynamic simulations